2015
DOI: 10.1007/s13277-015-3574-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prediction-score model for distant metastasis in nasopharyngeal carcinoma treated with intensity-modulated radiotherapy

Abstract: The objective of this study is to identify the risk factors and construct a prediction-score model for distant metastasis (DM) in nasopharyngeal carcinoma (NPC) patients treated with intensity-modulated radiotherapy (IMRT). A total of 520 nonmetastatic NPC patients were analysed retrospectively. The independent risk factors for DM were tested by multivariate Cox regression analysis. The prediction-score model was established according to the regression coefficient. The median follow-up was 88.4 months. The 5-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
10
27
1
Order By: Relevance
“…Abnormal LDHA expression is universal in many human cancers, such as pancreatic cancer [31], hepatocellular carcinoma [32], and breast cancer [33], suggesting that the overexpression of this gene promotes cancer development and progression. LDHA is reported to be an adverse independent prognostic factor for NPC [34]. In our present study, the LDHA level was elevated, and correlated with the TNM and clinical stage in NPC tissue samples.…”
Section: Discussionsupporting
confidence: 69%
“…Abnormal LDHA expression is universal in many human cancers, such as pancreatic cancer [31], hepatocellular carcinoma [32], and breast cancer [33], suggesting that the overexpression of this gene promotes cancer development and progression. LDHA is reported to be an adverse independent prognostic factor for NPC [34]. In our present study, the LDHA level was elevated, and correlated with the TNM and clinical stage in NPC tissue samples.…”
Section: Discussionsupporting
confidence: 69%
“…We showed that radiomics features complemented the TNM staging system, helping to provide better prognostic ability for pretreatment PFS. This complementary ability illustrates the clinical importance of our findings as TNM staging is routinely used in clinical practice (35,36). Currently, the TNM staging system is used for risk stratification and treatment decision making.…”
Section: Discussionsupporting
confidence: 55%
“…[29] Another study demonstrated that NLR > 2.81 was a significant adverse independent predictive factor for DM. [30] However, in our study, the pretreatment LMR value and pretreatment NLR were not statistically significant by multivariate analysis, although its P -value was <.05 by univariate analysis. The relationship between these 2 factors and metastasis of NPC remains to be further explored.…”
Section: Discussioncontrasting
confidence: 75%
“…[27,28] We also found a few studies have examined the relationship between NLR and DM in cancer patients. [22,29,30] One found that NLR > 5 predicts shorter overall survival in patients with head and neck squamous cell carcinoma. [29] Another study demonstrated that NLR > 2.81 was a significant adverse independent predictive factor for DM.…”
Section: Discussionmentioning
confidence: 99%